Sweet tooth [compact disc, unabridged] - McEwan, Ian (Recorded Books, 2012)
Britain, 1972. Serna Frome, a compulsive reader of novels, is sent on a "secret mission" which brings her into the literary world of Tom Haley, a promising young writer. First she loves his stories, then she begins to love the man. Can she maintain the fiction of her undercover life?